Optimization of weld parameters in wire and arc-based directed energy deposition of high strength low alloy steels - Le, Van Thao; Mai, Dinh Si; Dang, Van Thuc; Dinh, Duc Manh; Cao, Thi Hong; Nguyen, Van Anh (Taiwan Association of Engineering and Technology Innovation, 2022)
This paper aims to investigate the fabrication of high strength low alloy (HSLA) steels by wire and arc-based directed energy deposition (WADED). Firstly, the relationship between the process variables (including the travel speed-V, the current-C, and the voltage-U) and the geometrical characteristics of weld beads (including the bead height (BH), bead width (BW), and melting pool length (MPL)) was investigated. Secondly, the optimal process variables were identified using the desirability approach. The results indicate that voltage-U has the highest impact on BW and MPL, meanwhile the travel speed-V is the most impacting factor on BH. The optimal variables for the WADED process of HSAL steels are V = 0.3 m/min, C = 160 A, and U = 19 V. The component fabricated with the optimal variables is fully dense without spatters and defects, confirming the efficiency of the WADED process for HSLA steels.
Keywords: WADED; HSLA steel; weld bead; optimal variables